Implementasi Firebase Cloud Messaging untuk Meningkatkan Efisiensi Pencatatan Keuangan pada Aplikasi Android SmartMoney - Putri Cahyaning Tyas; Arif Iman Anshori; Abdul Razak Naufal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Personal money management is often overlooked by most people, irregular financial management often results in a mismatch between income and expenses, thus triggering uncontrolled spending. This study ims to improve the efficiency of user habits in recording finances by implementing a reminder (notification) feature using Firebase Cloud Messaging (FCM) on the SmartMoney application. The data collection method for this study uses questionnaires and research, based on an initial survey conducted by distributing questionnaires, as many as 73% of them rarely record transactions because they forget and feel the manual recording process is inefficient. The SmartMoney application development process uses the Incremental Development method, Meanwhile, functional testing was conducted using the Black Box Testing method to check the extent to which reminder messages were successfully received under various application usage conditions. Testing was carried out 10 times per device for a total of 30 trials. The test results showed that notification messages were successfully delivered 95% of the 30 trials, whether the application was running in the foreground, background, or had been completely closed. The implementation of FCM has proven effective in providing transaction information directly to users (Killed). Therefore, this study shows that the implementation of Firebase Cloud Messaging (FCM) is able to create effective and consistent push notification (Notification Reminder) feature for users so that it can increase the efficiency of more orderly financial recording.